Ultrasound Evaluation of the Impact of Disparities of the Pulsatility Indices on Fetal Outcomes in Preeclamptic Pregnancies: A Pilot Study from a Tertiary Hospital in South South Nigeria - Akagbue, Vivian N; Ugboma, Enighe Wananyo (International Journal of Innovative Research in Medical Science, 2024)
Objective: To examine the relationships between fetal Doppler indices and perinatal outcomes in women with preeclampsia and normotensive controls. Methods: Middle cerebral artery (MCA) pulsatility index (PI), umbilical artery (UA) PI, and cerebroumbilical PI ratio were measured in women with preeclampsia (n=50) and normotensive controls (n=50). Associations with birth weight, gestational age at delivery, and 1- and 5-minute Apgar scores were evaluated. Predictive accuracy of indices for adverse outcomes was also assessed. Results: In pre-eclamptics, MCA PI correlated with birth weight, Apgar scores, and gestational age (p<0.05). UA PI correlated negatively with all outcomes (p<0.05). Cerebroumbilical ratio correlated positively with birth weight and Apgar scores, and negatively with gestational age and 1-minute Apgar (p<0.05). UA PI demonstrated high sensitivity and specificity for predicting outcomes except prematurity. Cerebroumbilical ratio showed balanced sensitivity and specificity except for stillbirths. Conclusions: Fetal Doppler indices provide valuable prognostic information in preeclampsia. UA PI may be optimal for predicting adverse outcomes. Cerebroumbilical ratio balances sensitivity and specificity. Larger multicenter studies are needed to standardize criteria and validate predictive accuracy across disease severity. Fetal Doppler surveillance warrants further research to optimize preeclampsia management.